Impacts of Mobile Phone Distractions on Walking Performance - Gjergji Selamaj (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2020)
This work studies the effect of playing mobile phones while walk-ing to pedestrian safety. Thirty young-adults were observed while walking around Skanderbeg square with and without playing Pokemon GO. Results show that the walking performance deteri-orated when the participants played Pokemon GO as can be seen from the average number of laps decreased from 2.47 to 1.58 laps, the average number of collisions increased from 0.27 to 3.93, and the average number of slip, trip and fall increased from 0.03 to 2.07. It can be concluded that using mobile phone while walking could be dangerous for pedestrian safety.